MALDI-MS-based imaging of small molecules and proteins in tissues - Reyzer, Michelle L; Caprioli, Richard M (Current opinion in chemical biology, 2007)
The direct analysis of tissues using matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) enables both endogenous and exogenous compounds present in tissues to be detected with molecular specificity while maintaining their spatial orientation. This unique combination, coupled with excellent sensitivity and rapid analysis time, presents many potential advantages to a wide range of applications in diverse biological fields. Recent advances have shown how the technique can be applied to cancer research, neuroscience and pharmaceutical development. Examples include the use of unique protein profiles to classify human tumor tissues and predict patient outcomes, the discovery of protein changes in mouse cerebellum as a function of development, and the two-dimensional visualization of the distribution of a drug and first-pass metabolites in rat whole-body sections.